Peroxiredoxin 2, glutathione peroxidase, and catalase in the cytosol and membrane of erythrocytes under H2O2-induced oxidative stress. (August 2015) - Rocha, S.; Gomes, D.; Lima, M.; Bronze-da-Rocha, E.; Santos-Silva, A.
Abstract: Erythrocytes are continuously exposed to risk of oxidative injury due to oxidant oxygen species. To prevent damage, they have antioxidant agents namely, catalase (Cat), glutathione peroxidase (GPx), and peroxiredoxin 2 (Prx2). Our aim was to contribute to a better understanding of the interplay between Prx2, Cat, and GPx under H2 O2 -induced oxidative stress, by studying their changes in the red blood cell cytosol and membrane, in different conditions. These three enzymes were quantified by immunoblotting. Malondialdehyde, that is, lipoperoxidation (LPO) in the erythrocyte membrane, and membrane-bound hemoglobin (MBH) were evaluated, as markers of oxidative stress. We also studied the erythrocyte membrane protein profile, to estimate how oxidative stress affects the membrane protein structure. We showed that under increasing H2 O2 concentrations, inhibition of the three enzymes with or without metHb formation lead to the binding of Prx2 and GPx (but not Cat) to the erythrocyte membrane. Prx2 was detected mainly in its oxidized form and the linkage of metHb to the membrane seems to compete with the binding of Prx2. Catalase played a major role in protecting erythrocytes from high exogenous flux of H2 O2, since whenever Cat was active there were no significant changes in any of the studied parameters. When only Cat was inhibited, Prx2 and GPx were unable to prevent H2 O2 -induced oxidative stress resulting in increasing MBH and membrane LPO. Additionally, the inhibition of one or more of these enzymes induced changes in the anchor/linker proteins of the junctional complexes of the membrane cytoskeleton–lipid bilayer, which might lead to membrane destabilization.